The Commercial Consequences of Collective Layoffs: Close the Plant, Lose the Brand? - Landsman, Vardit; Stremersch, Stefan (Journal of Marketing, 2020)
This article examines the effects of collective layoff announcements on sales and marketing-mix elasticities, accounting for supply-side constraints. The authors study 205 announcements in the automotive industry using a difference-in-differences model. They find that, following collective layoff announcements, layoff firms experience adverse changes in sales, advertising elasticity, and price elasticity. They explore the moderating role of announcement characteristics on these changes and find that collective layoff announcements by domestic firms and announcements that do not mention a decline in demand as a motive are more likely to be followed by adverse marketing-mix elasticity changes. On average, sales for the layoff firm in the layoff country are 8.7% lower following a collective layoff announcement than their predicted levels absent the announcement. Similarly, advertising elasticity is 9.8% lower and price elasticity is 19.2% higher than absent the announcement. Conversely, layoff firms typically decrease advertising spending in the country where collective layoffs have occurred, yet they do not change prices. These findings are relevant to marketing managers of firms undergoing collective layoffs and to analysts of collective layoff decisions.